Safety and protective capability of an inactivated SARS-CoV-2 vaccine on pregnancy, lactation and the growth of offspring in hACE2 mice. Issue 32 (30th July 2022) - Lin, Kaili; Liu, Meixuan; Bao, Linlin; Lv, Qi; Zhu, Hua; Li, Dan; Xu, Yanfeng; Xiang, Zhiguang; Liu, Jiangning; Liang, Xujian; Han, Yunlin; Cong, Zhe; et al.
Abstract: The mass inoculation of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine to induce herd immunity is one of the most effective measures to fight COVID-19. The vaccination of pregnant women cannot only avoid or reduce the probability of infectious diseases, but also offers the most effective and direct protection for neonates by means of passive immunization. However, there is no randomized clinical data to ascertain whether the inactivated vaccination of pregnant women or women of childbearing age can affect conception and the fetus. We found that human angiotensin-converting enzyme 2 (hACE2) mice that were vaccinated with two doses of CoronaVac (an inactivated SARS-CoV-2 vaccine) before and during pregnancy exhibited normal weight changes and reproductive performance indices; the physical development of their offspring was also normal. Following intranasal inoculation with SARS-CoV-2, pregnant mice in the immunization group all survived; reproductive performance indices and the physical development of offspring were all normal. In contrast, mice in the non-immunization group all died before delivery. Analyses showed that inoculation of CoronaVac was safe and did not exert any significant effects on pregnancy, lactation, or the growth of offspring in hACE2 mice. Vaccination effectively protected the pregnant mice against SARS-CoV-2 infection and had no adverse effects on the growth and development of the offspring, thus suggesting that inoculation with an inactivated SARS-CoV-2 vaccine may be an effective strategy to prevent infection in pregnant women.